Multimodal Literature in ELT: Theory and Practice - Maria Eisenmann; Theresa Summer (CLELEjournal, 2020)
On the basis of five pedagogical principles, Maria Eisenmann and Theresa Summer make the case for integrating multimodal texts in ELT so that language learners gain an insight into how to read a multimodal text and are potentially motivated to choose this text format during out-of-school reading.